Public Librarians Reflect Belief in Intellectual Freedom through Collection Development Activities - Goertzen, Melissa (Evidence Based Library and Information Practice, 2016)
A Review of: Oltmann, S. M. (2016). Public Librarians' Views on Collection Development and Censorship. Collection Management, 41(1), 23-44. http://dx.doi.org/10.1080/01462679.2015.1117998 Objective – To examine public librarians’ perspectives on censorship and intellectual freedom in relation to collection development activities. Design – Survey combining questions from previous studies by Moody (2004) and Harkovitch, Hirst and Loomis (2003) with additional questions regarding intellectual freedom and demographics. Setting – Public libraries in the State of Ohio. Subjects – 251 directors and librarians responsible for collection development. Methods – The researcher created a survey in Qualtrics, a software that supports online data collection and analysis. It contained thirty-two structured and open-ended questions and took approximately 15-25 minutes to complete. To recruit participants, an explanatory letter and survey link were sent to every public library director in the State of Ohio. Directors were also asked to share the survey with librarians under their leadership who were responsible for collection development. To analyze the data set, cross-tabulations were run to identify statistically significant correlations between demographic and community variables. Main Results – The response rate was 43% (108 out of 251). Participants agreed with the American Library Association’s (ALA) definition of intellectual freedom, and to build collections that neither promote nor suppress specific ideas or beliefs. Only 3.7% of respondents reported decisions not to purchase materials due to fear of negative feedback from the community. Nearly 40% of participants reported conflict between personal and professional values at some time. All said that this dilemma had no bearing on professional collection development decisions. Contrary to anecdotal evidence that suggests librarians in rural or conservative communities are less likely to purchase controversial materials, the researcher found that community and political variables were not statistically significant; across the board, participants were most concerned with building balanced, well-developed collections. Gender, however, was statistically significant in terms of pressures felt to restrict access to materials; male librarians reported a higher number of instances where they felt internal or external pressures of this nature. However, as the number of male respondents was relatively low (15 out of 108 participants), the researcher did not draw concrete conclusions as to why this discrepancy exists. Conclusion – Study findings demonstrate a strong professional allegiance to intellectual freedom as defined by the ALA. In a practical sense, the participant group applied the principles of intellectual freedom to collection development activities regardless of demographic, community, or political variables.